Regulating the electronic structure through charge redistribution in dense single-atom catalysts for enhanced alkene epoxidation - Jin, Hongqiang; Zhou, Kaixin; Zhang, Ruoxi; Cui, Hongjie; Yu, Yu; Cui, Peixin; Song, Weiguo; Cao, Changyan (Nature communications, 2023)
Inter-site interaction in densely populated single-atom catalysts has been demonstrated to have a crucial role in regulating the electronic structure of metal atoms, and consequently their catalytic performances. We herein report a general and facile strategy for the synthesis of several densely populated single-atom catalysts. Taking cobalt as an example, we further produce a series of Co single-atom catalysts with varying loadings to investigate the influence of density on regulating the electronic structure and catalytic performance in alkene epoxidation with O 2 . Interestingly, the turnover frequency and mass-specific activity are significantly enhanced by 10 times and 30 times with increasing Co loading from 5.4 wt% to 21.2 wt% in trans-stilbene epoxidation, respectively. Further theoretical studies reveal that the electronic structure of densely populated Co atoms is altered through charge redistribution, resulting in less Bader charger and higher d-band center, which are demonstrated to be more beneficial for the activation of O 2 and trans-stilbene. The present study demonstrates a new finding about the site interaction in densely populated single-atom catalysts, shedding insight on how density affects the electronic structure and catalytic performance for alkene epoxidation. The interaction among single sites in densely populated single-atom catalysts (SACs) has received much attention. Here the authors report a general and facile strategy for the synthesis of several densely populated SACs and decipher the influence of density on regulating their electronic structure and catalytic performance in alkene epoxidation.